WOMEN’S ALLEGORIES IN ESTELITO B. JACOB’S PINAGROK - Santiano, Christine U (SIGEH ELT : Journal of Literature and Linguistics, 2025)
This study aimed to analyze the Women’s Allegories in Estelito B. Jacob’s Pinagrok, an anthology of poems, as a basis for the development of a supplementary learning material in English 10. Specifically, it sought answers to the following questions: 1) What dominant themes are present in the poetry? and 2) What personal dilemmas and societal conflicts are evident in Estelito B. Jacob’s Pinagrok? This study used qualitative design specifically the descriptive method and focused on the thematic analysis of the 43 selected poems. This study was premised on the assumptions that (1) The dominant themes in Estelito B. Jacob’s Pinagrok revolve around women’s allegories and (2) There are personal dilemmas and societal conflicts evident in the poetry. Based on the analysis and interpretation of the selected poems, the following were found out: 1) There are 14 dominant themes present in the poetry such as emotional distress, submissiveness, sexual objectification, sacrifice, prostitution, sexual abuse, discrimination, incest, poverty, infidelity, physical abuse, bravery, unrequited love, domestic violence; and 2) There are 11 personal dilemmas evident in the poetry such as indecisiveness, confusion, rejection, helplessness, vulnerability, guilt, distrust, injustice, grief, fear, and insecurity. Moreover, there are 10 societal conflicts present in the poetry namely infidelity, cooperative stress, intolerance and exclusion, sexual violence, negative influence, norms, economic status and stability, injustice, presumptuousness, and labelling. Based on the findings, the following conclusions were drawn: (1) The themes reflect the lived experiences of women highlighting their struggles in a patriarchal society and (2) There is interconnectedness between individual struggles and structural inequalities, providing a nuanced understanding of the societal dynamics influencing human experiences. Hence, the following recommendations are made: (1) Teachers may integrate the 14 identified feminist themes into classroom discussions and activities to foster a deeper understanding of social issues and promote critical thinking among students and (2) Teachers may use activities and discussions that highlight the intersection of personal dilemmas and societal conflicts to help students relate to real-life struggles while fostering empathy and problem-solving skills.